ÚLKEN JARÍLÍW TEORIYASÍNDA ÁLEMNIŃ PAYDA BOLÍWÍNÍŃ HÁZIRGI ZAMAN TÚSINIGI - Jumamuratov, A. (SCIENCE and SOCIETY, 2025)
After the presidential decision to mark the 630th anniversary of the birth of Mirza Ulugbek, the next developments in astronomy were dedicated to the theory of the big bang in the beginning of the universe.